Comparison of the BacT/Alert PF Pediatric FAN Blood Culture Bottle with the Standard Pediatric Blood Culture Bottle, the Pedi-BacT - Krisher, Karen K. (American Society for Microbiology, 2001)
The performance of the BacT/Alert PF (Organon-Teknika Corp., Durham, N.C.), a new nonvented pediatric FAN blood culture bottle, was compared to that of the original pediatric bottle, the Pedi-BacT, with matched aerobic cultures obtained from two separate facilities. A total of 244 clinically significant isolates were recovered from 4,015 compliant pairs. Among the positive cultures, 170 (70%) isolates were detected in both the BacT/Alert PF and the Pedi-BacT bottles, while 47 (19%) isolates were recovered in the BacT/Alert PF bottle only and 27 (11%) isolates were recovered in the Pedi-BacT bottle only. Although isolation of specific microorganisms was comparable for the two bottles, the total number of organisms recovered by the BacT/Alert PF was greater than that by the Pedi-BacT (P = 0.0272). In addition, more organisms were recovered by the BacT/Alert PF bottle from the blood of patients receiving antimicrobial therapy (P = 0.0180). Overall time to detection was similar for the two bottles; however, a significantly decreased mean time to detection was recorded for yeast from the BacT/Alert PF bottle (22.9 h; P = 0.0001) and staphylococci from the Pedi-BacT bottle (22.5 h; P = 0.0056). One false-negative culture and five false-positive cultures occurred with the Pedi-BacT bottle, compared to one false-positive culture with the BacT/Alert PF bottle. The BacT/Alert PF bottle is a reliable blood culture bottle for pediatric blood culture specimens and may offer improved recovery of microbes from patients on antimicrobial therapy. The use of the nonvented bottle will both facilitate bottle processing and decrease expenditures for materials due to the elimination of the venting needles required for the original vented bottles.